Analysis of nutlet morphological characteristics of some Iranian Ajuga L. taxa - Sayed Mehdi Talebi; RAHELEH TABARIPOUR; MAJID ESKANDARI (Society for Indonesian Biodiversity, 2019)
Abstract. Talebi SM, Tabaripour R, Eskandari M. 2019. Analysis of nutlet morphological characteristics of some Iranian Ajuga L. taxa. Biodiversitas 20: 2833-2840. Ajuga is one of the problematic Lamiaceae genera, which naturally grows in different parts of Iran. There are many discussions about infrageneric and infraspecific classifications of the genus and several synonyms were definite for its taxa. In the current study, we evaluated nutlet morphological characteristics from six Iranian taxa of the genus using Scanning Electron Microscopy (SEM) and Light microscopy (LM). In total, thirteen (four qualitative and nine quantitative) nutlet morphological variables were investigated, and the obtained data were analyzed using MVSP and SPSS software. Quantitative nutlet features varied among the studied taxa and ANOVA test revealed significant variations (P <0.01) for most of them. Moreover, PCA analysis showed some characteristics made more than 60% of variations. Some quantitative characteristics like nutlet and ventral sculpturing shapes were nearly stable among the taxa. But dorsal sculpturing shape and existence of exocarp cell indumentum highly varied among the taxa and could be used as distinguishing traits for identification of taxa. The studied taxa were divided into four groups in UPGMA dendrogram and also PCA and PCO plots of the nutlet features. CA. Joined plot revealed that each group had specific nutlet characteristic (s). Taxa arrangements were not similar to those have been definite for them in Flora Iranica and Flora of Iran. Furthermore, some infraspecific taxa must be redefinite. It is advised to use complementary molecular studies to better clearing species relationship, taxa position and rank in the genus.